Temporary employment and counteracting the abuse of a fixed-term employment contract - Moras-Olaś, Kinga (Temporary employment as an atypical form of employment: No. 19/2022, 2022)
The regulation concerning the prevention of the abuse of a fixed-term employment contract included in the Labour Code does not apply to temporary work in Polish law. This does not mean, however, that the abuse cannot occur in this type of employment as well. The article examines where the phenomenon of abuse occurs within the three-way relationship in temporary employment. It was found that the source of the abuse is the legal relationship between the employer-user and the temporary-employment agency. At the same time, the statutory mechanisms limiting temporary employment are mechanisms to counteract these abuses.